Survival of patients with small cell lung cancer undergoing lung resection in England, 1998–2009. Issue 3 (30th October 2013) - Lüchtenborg, Margreet; Riaz, Sharma P; Lim, Eric; Page, Richard; Baldwin, David R; Jakobsen, Erik; Vedsted, Peter; Lind, Mike; Peake, Michael D; Mellemgaard, Anders; Spicer, James; Lang-Lazdunski, Loic; et al.
Abstract : Introduction: Chemotherapy or chemoradiotherapy is the recommended treatment for small cell lung cancer (SCLC), except in stage I disease where clinical guidelines state there may be a role for surgery based on favourable outcomes in case series. Evidence supporting adjuvant chemotherapy in resected SCLC is limited but this is widely offered. Methods: Data on 359 873 patients who were diagnosed with a first primary lung cancer in England between 1998 and 2009 were grouped according to histology (SCLC or non-SCLC (NSCLC)) and whether they underwent a surgical resection. We explored their survival using Kaplan–Meier analysis and Cox regression, adjusting for age, sex, comorbidity and socioeconomic status. Results: The survival of 465 patients with resected SCLC was lower than patients with resected NSCLC (5-year survival 31% and 45%, respectively), but much higher than patients of either group who were not resected (3%). The difference between resected SCLC and NSCLC diminished with time after surgery. Survival was superior for the subgroup of 198 'elective' SCLC cases where the diagnosis was most likely known before resection than for the subgroup of 267 'incidental' cases where the SCLC diagnosis was likely to have been made after resection. Conclusions: These data serve as a natural experiment testing the survival after surgical management of SCLC according to NSCLC principles. Patients with SCLC treated surgically for early stage disease may have survival outcomes that approach those of NSCLC, supporting the emerging clinical practice of offering surgical resection to selected patients with SCLC.